(untitled) (LEARNing Landscapes, 2022)
This paper showcases how a reflexive practice, that includes arts-based activities, deepened understandings experienced by a doctoral student of psychology while completing the data analysis section of a metasynthesis. The metasynthesis focused on qualitative studies, examining the mental and spiritual care of persons living with diabetic foot ulcers. Reflecting on the experience, this work argues for spaces where researchers stop and engage in reflexivity, making the work more robust.